Vocational interests and cognitive aptitudes for learning in school adolescents - Panduro, José Antonio (2021)
In order to establish the relationship between vocational interests and cognitive aptitudes for learning in adolescent school students, and to establish correlations within each variable and perform comparisons according to gender, a sample of 61 third year high school students from a private school from Lima, Peru (27 men and 34 women, aged between 14 and 15 years) were evaluated with the Talento 3 Test (based on Holland’s theory, RIASEC) and four subtests of BADyG-M (chosen to evaluate Attention/Discrimination, Auditory Memory, Spatial Orientation, Logical Reasoning). The results indicate significant correlations that demonstrate the autonomy of vocational interests of Holland’s theory, and also support Hogan’s model; comparisons between genders indicate averages significantly higher in men in the Entrepreneur and Conventional interests, whereas women’s averages in Artistic and Social was higher. In cognitive aptitude for learning highly significant correlations between Attention/Discrimination, Spatial Orientation and Logical Reasoning were found, suggesting the presence of a general factor, noted by the theories of the structure of intelligence; no differences between genders for any of the aptitudes were found. Finally, to link the two variables, an inverse association between aptitude Attention/Discrimination and Artistic interest, and a direct association between the Entrepreneur interest and aptitudes Attention/Discrimination and Spatial Orientation were found. The importance of these data for career advice and educational guidance is highlighted.